Isolation and screening of endophytic bacteria from Ngoc Linh ginseng (Panax vietnamensis Ha et Grushv) for biosynthesis β-glucosidase - Tam, Nguyen Thi; Tam, Nguyen Phu; Nguyen, Vu Thi Hanh; Hung, Nguyen Khac; Huy, Chu Nhat; Ngoc, Pham Bich; Ha, Chu Hoang; Tien, Phi Quyet (Academia Journal of Biology, 2018)
Biotransformation of secondary metabolites from medicinal plants by bacteria has been studied extensively in the recent years. One of the potential sources for screening bacteria is plant endophytic bacteria. In this study, we isolated and screened endophytic bacteria for transformation of ginsenoside Rb1 of Ngoc Linh ginseng collected at village number 2, Tra Linh commune, Nam Tra My district, Quang Nam province. There are 45 strains isolated form rhizobium (24 strains), petioles (8 strains) and leaves (13 strains). After screening, there are 27 strains positive with β-glucosidase test, an enzyme which catalyses the hydrolysis of terminal non-reducing residues in β-glucosides-aglycone linkage of ginsenoside Rb. By evaluating the β-glucosidase activity and identification via 16S rRNA sequence, we choosed four high β-glucosidase acitivity strains SVK32 (Enterobacter sp.); SVK34 (Serratia sp.); SVK37 (Ochrobactrum sp.) and SVK44 (Arthrobacter sp.) for futher study on biotransformating of ginsenoside Rb1 into ginsenoside Rd and Rg3.